Oil‐Soluble Polymer Brush Grafted Nanoparticles as Effective Lubricant Additives for Friction and Wear Reduction. Issue 30 (6th June 2016) - Wright, Roger A. E.; Wang, Kewei; Qu, Jun; Zhao, Bin
Abstract: The development of high performance lubricants has been driven by increasingly growing industrial demands and environmental concerns. Herein, we demonstrate oil‐soluble polymer brush‐grafted inorganic nanoparticles (hairy NPs) as highly effective lubricant additives for friction and wear reduction. A series of oil‐miscible poly(lauryl methacrylate) brush‐grafted silica and titania NPs were synthesized by surface‐initiated atom transfer radical polymerization. These hairy NPs showed exceptional stability in poly(alphaolefin) (PAO) base oil; no change in transparency was observed after being kept at −20, 22, and 100 °C for ≥55 days. High‐contact stress ball‐on‐flat reciprocating sliding tribological tests at 100 °C showed that addition of 1 wt % of hairy NPs into PAO led to significant reductions in coefficient of friction (up to ≈40 %) and wear volume (up to ≈90 %). The excellent lubricating properties of hairy NPs were further elucidated by the characterization of the tribofilm formed on the flat. These hairy NPs represent a new type of lubricating oil additives with high efficiency in friction and wear reduction. Abstract : Oil‐soluble polymer brush grafted nanoparticles (hairy NPs) were synthesized and evaluated as lubricant additives. These hairy NPs exhibited exceptional stability in a lubricating base oil at both low and high temperatures. High contact stress tribological tests at 100 °C revealed that the addition of 1 wt % of hairy NPs into the oil led to significant reductions in friction and wear volume.